DOP47 Sustained remission in patients with moderate to severe ulcerative colitis: Results from the Phase 3 UNIFI maintenance study. (25th January 2019) - Van Assche, G; Targan, S R; Baker, T; O'Brien, C D; Zhang, H; Johanns, J; Szapary, P; Marano, C; Leong, R W; Rowbotham, D; Hisamatsu, T; Danese, S; et al.
Abstract: Background: The UNIFI randomised-withdrawal maintenance study evaluated the safety and efficacy of subcutaneous (SC) ustekinumab in patients with moderately to severely active ulcerative colitis (UC) who had responded to intravenous (IV) ustekinumab during induction. In this analysis, we describe the durability of remission through maintenance Week 44. Methods: At Week 0 of the maintenance study, 523 patients who had responded to IV ustekinumab induction were randomly assigned in a 1:1:1 ratio to placebo SC, ustekinumab SC 90 mg q12w, or ustekinumab SC 90 mg q8w. Although maintenance of clinical remission at Week 44 was a major secondary endpoint (reported elsewhere), partial Mayo scores, rectal bleeding, and stool frequency Mayo subscores, endoscopic healing, and Inflammatory Bowel Disease Questionnaire (IBDQ) scores were also used to assess remission at the level of patient-reported symptoms, endoscopy, and health-related quality of life (see Table for definitions). Results: At baseline of the maintenance study, the proportions of patients in symptomatic remission and IBDQ remission were generally similar among the treatment groups (Table). The proportion of patients with endoscopic healing at baseline was lower in the ustekinumab q8w group (32.4%) compared with the ustekinumab q12w (39.5%) and placebo groups (40.6%). Through Week 44, the proportions of patients in partial Mayo remission were sustained in the ustekinumab treatment groups, while the proportion of patients in the placebo group decreased, with consistent numerical separation from the ustekinumab q8w group by Week 8 and the q12w group by Week 16 (Figure). In addition, significantly greater proportions of patients in the ustekinumab q8w and q12w groups compared with placebo maintained symptomatic remission and IBDQ remission through Week 44 and maintained endoscopic healing at Week 44 among patients who achieved each respective endpoint at maintenance baseline. Similarly, greater proportions of ustekinumab-treated patients had durable partial Mayo remission through Week 44 compared with placebo. Conclusions: Both doses of ustekinumab SC maintenance therapy sustained remission, measured by patient-reported symptoms and endoscopic and quality of life assessments, in patients with moderately to severely active UC.